EFFECT OF APPLIED BEHAVIOUR ANALYSIS ON SOCIAL SKILLS AND ACADEMIC ACHIEVEMENT OF PUPILS WITH AUTISM SPECTRUM DISORDER - Ebere Adimora, Dorothy; Mamudu Adene, Friday; Obiageli Omeje, Monica; Ngozi Ejiofor, Juliana; Eberechukwu Offordile, Edmund (International Journal of Psychosocial Rehabilitation, 2021)
Objectives: Autism is a chronic neurodevelopmental disorder. The study investigated theprevalence of autism spectrum disorder (ASD) amongst primary school pupils in Enugu State,Nigeria.Design: Pretest-Posttest non-equivalent control group design, with the experimental groupadopting applied behaviour analysis (ABA) intervention and the control group usingconventional method.Materials and Methods: Two research questions and two null hypotheses guided the study.The population comprised all the pupils identified with ASD in Enugu State, Nigeria. Thesample comprises 36 pupils identified with ASD in schools used. The instruments wereobservation schedule, semi-structured interview schedule and 4- point Likert-typequestionnaire administered to elicit information on pupils’ social skills while their academicachievement test scores were used to ascertain their academic achievement. Researchquestions were analysed using mean and standard deviation while the hypotheses were testedusing analysis of covariance (ANCOVA) statistic at 0.05 probability level.Results: The results showed that exposing pupils with ASD to ABA intervention boosted theirsocial skills and academic achievement scores. Parents of children exposed to intensive ABA,report greater reductions in daily stress than parents of children with other treatments.Conclusions: exposing pupils with ASD to ABA is efficacious in enhancing their social skillsand academic achievement